Nucleic acid vaccine candidates encapsulated with mesoporous silica nanoparticles against MERS-CoV - Iman Almansour; B. Rabindran Jermy (Human Vaccines & Immunotherapeutics)
Middle East respiratory coronavirus (MERS-CoV) is a newly emergent, highly pathogenic coronavirus that is associated with 34% mortality rate. MERS-CoV remains listed as priority pathogen by the WHO. Since its discovery in 2012 and despite the efforts to develop coronaviruses vaccines to fight against SARS-CoV-2, there are currently no MERS-CoV vaccine that has been approved. Therefore, there is high demand to continue on the development of prophylactic vaccines against MERS-CoV. Current advancements in vaccine developments can be adapted for the development of improved MERS-CoV vaccines candidates. Nucleic acid-based vaccines, including pDNA and mRNA, are relatively new class of vaccine platforms. In this work, we developed pDNA and mRNA vaccine candidates expressing S.FL gene of MERS-CoV. Further, we synthesized a silane functionalized hierarchical aluminosilicate to encapsulate each vaccine candidates. We tested the nucleic acid vaccine candidates in mice and evaluated humoral antibodies response. Interestingly, we determined that the non-encapsulated, codon optimized S.FL pDNA vaccine candidate elicited the highest level of antibody responses against S.FL and S1 of MERS-CoV. Encapsulation of mRNA with nanoporous aluminosilicate increased the humoral antibody responses, whereas encapsulation of pDNA did not. These findings suggests that MERS-CoV S.FL pDNA vaccine candidate induced the highest level of humoral responses. This study will enhance further optimization of nanosilica as potential carrier for mRNA vaccines. In conclusion, this study suggests MERS-CoV pDNA vaccine candidate as a suitable vaccine platform for further pivotal preclinical testings.